Isolation of Methicillin-Resistant Coagulase-Negative Staphylococci from Hemodialysis Patients in Al-Najaf Province - Oday Mitib Hadi; Ihsan Khadum Humaidy (Indian Journal of Forensic Medicine & Toxicology, 2021)
Information about methicillin-resistant coagulase-negative staphylococci (CoNS) is unavailable in ourprovince, in comparison with methicillin-resistant Staphylococcus aureus. Two hundred and forty isolates ofStaphylococci were recovered from hemodialysis patients, from July-2019 to January-2020. Antimicrobialsusceptibility was performed for methicillin-resistant CoNS, by using the Kirby and Bauer technique.mecA gene was detected by polymerase chain reaction (PCR). The results revealed that the infections werepredominant in males (66.7%) especially in the age group more than 60 years old. Patients from urban areasoccupied the highest percent in comparison with the rural areas.Staphylococcus epidermidis was predominant among other isolated genera (63.33%), of these forty strains(26.32%) were mecA positive, while Staphylococcus saprophyticus takes only (16.67%) and six isolates wereappeared to be mecA positive. Resistant patterns illustrated that most mecA positive strains were resistant tomore than one antibiotic of none-beta lactam antibiotics especially rifampin (60.87%).In conclusion, the increase of the antibiotic-resistant by coagulase-negative staphylococci, and in particularmec A gene containing CoNS, is a risk factor for residents of the holy city of Najaf.